Empire Seen from Within. Cinema Objects, Spaces and Edifices in the Limelight in Colonial India and Ceylon (1899-1950) - Vilasnee Tampoe-Hautin (Cahiers Victoriens et Edouardiens)
While research on material culture has focused abundantly on objects of everyday life as a way of observing societies and understanding our past, only in recent times has it concerned itself with the study of those related to cinema, one of the ‘more readily consumable forms of entertainment’ (MacKenzie 2), which came out of the late 19th century workshops of the geniuses of the day, Edison, Urban or Lumière. And yet, nowhere is it more relevant to include conventional cinema hardware in scientific research given that in the first instance, cinema as an art, but also an industry with a massive following, came accompanied by a vast array of optical, audio and mechanical devices. Further, it was the Victorians and the Edwardians who bequeathed us the first objects, edifices and spaces of cinema, adding to the iconic and material wealth characteristic of the age. The scope widens further for research when one contemplates the way technical innovations in Europe, first in photography, then in picture animation as well as in printing and reproducing fixed or moving images, contributed eminently to the promotion of Empire within Empire, in what Michel Foucault qualified as a fin de siècle ‘frénésie neuve des images’ (Exhibition catalogue of Gérard Fromanger’s ‘Le désir est partout’, 1975, Leutrat). I will venture down this less beaten track in what will also be a reverse perspective. I will consider the way the inhabitants, both indigenous and expatriate, of the British colonies in the Indian Ocean (in particular Sri Lanka and India) engaged with cinema objects but also its sites and edifices (auditoriums and studios) which, from their architecture to their interior, also paid tribute to the splendour of Empire. How did objects, equipment and sites manage to secure bioscope a massive and captive market in every nook and cranny of the British Empire and either enhance or bear on the perception of Empire amongst the colonized? I will linger on those cross-cultural encounters of the most serendipitous kind between objects, ideas and individuals converging to bring reels on wheels to the edge of Empire: a WW1 British Army tent, a projector, a rifle and a gramophone hoisted onto a bullock cart, travelling through the jungles of colonial Ceylon, reminiscent of Leonard Woolf’s uncelebrated novels… Finally, although beyond the scope of this volume, the question has at least to be raised of the restoration of these devices, capable of producing images whose rich nuances remain to date unequalled by digital technology. The well-established film industry in South Asia with its high rate of cinema attendance, largely, though not exclusively in view of the gigantic Indian film industry, justifies that these issues be addressed and resolved urgently, both at the level of research as well as relevant authorities.